Students’ Error of Using Passive Voice Based on Surface Strategy Taxonomy - Suprapto, Suprapto; Richad Hasan, Jhems; Suzanne , Nina (ELOQUENCE : Journal of Foreign Language, 2022)
Background: Grammar errors are common because English grammar is still quite complicated to learn, including constructing sentences using the Passive Voice. Purpose: This research aims to identify mistakes in constructing sentences using Passive Voice by MAN Gorontalo Students to become a reference material in improving grammar learning. Method: This research uses a quantitative method. Data is collected through tests and documentation. The research population was 40 students of class X MAN Gorontalo and a sample of 20 students. Data analysis techniques go through four stages, data collection, data presentation, data reduction, and conclusion. Results and Discussion: This study concludes that there are four types of student errors based on the taxonomic strategy in using Passive Voice, namely: 1) addition error, 2) omission error, 3) misformation error, and 4) misordering error) and two types of errors based on communicative effect taxonomy; 1) global error and 2) local error. Conclusions and Implications: This research has implications that English teachers can analyze weaknesses in changing active voice into passive voice by practicing changing tense forms from past verbs for past activities and habitual information for ordinary activities. To correct errors in compiling sentences in passive voice, teachers must also do tutorial-based remedial teaching for passive voice material, especially on the misformation aspect, including assigning students to make a list of active and passive verbs and their use in compiling passive voice